2019
DOI: 10.1186/s12951-019-0494-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-membrane-biomimetic nanoparticles for targeted antitumor drug delivery

Abstract: Background Nanoscale drug-delivery systems (DDSs) have great promise in tumor diagnosis and treatment. Platelet membrane (PLTM) biomimetic DDSs are expected to enhance retention in vivo and escape uptake by macrophages, as well as minimizing immunogenicity, attributing to the CD47 protein in PLTM sends “ don’t eat me ” signals to macrophages. In addition, P-selectin is overexpressed on the PLTM, which would allow a PLTM-biomimetic DDS to specifically bind to the CD44 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 38 publications
0
114
0
Order By: Relevance
“…We also showed that curcumin has additional therapeutic benefits by using R/P-cGNS for cancer therapies including photothermal effects, controlled drug release at elevated temperature, and the targeting of cancer cells through PLTs. Recently, many trials have been implemented to study the use of the tumor-targeting properties of PLTs (Dehaini et al, 2017;Wang et al, 2019). PLTs primarily play an important role in hemostasis; the initial stage of hemostasis begins with the binding of activated platelets to the damaged vessels exposing von Willebrand factor (vWF), which prevents excessive bleeding (Yun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that curcumin has additional therapeutic benefits by using R/P-cGNS for cancer therapies including photothermal effects, controlled drug release at elevated temperature, and the targeting of cancer cells through PLTs. Recently, many trials have been implemented to study the use of the tumor-targeting properties of PLTs (Dehaini et al, 2017;Wang et al, 2019). PLTs primarily play an important role in hemostasis; the initial stage of hemostasis begins with the binding of activated platelets to the damaged vessels exposing von Willebrand factor (vWF), which prevents excessive bleeding (Yun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The solution was sonicated until complete dissolution was achieved, and then added dropwise into 5 mL of deionized water under stirring at 1000 rpm. After leaving the suspension to stand for 3 h to evaporate the acetone [32], 500 μL of the resulting NP suspension was set aside for electron microscopy, dynamic light scattering (DLS) and zeta potential analysis, and the rest was stored at 4 °C for further use.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the platelet membrane is generally obtained by a repeated freeze–thaw process [ 104 ]. According to Zhang’s research, they obtained platelet membrane through freezing aliquots of platelet suspensions at −80°C before thawing them to room temperature.…”
Section: Cell Membrane-camouflaged Npsmentioning
confidence: 99%